2021
DOI: 10.31883/pjfns/142835
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Anti-Initiation and Anti-Progression Properties of Sulphated-Extract of Colocasia esculenta

Abstract: Colocasia esculenta (Taro) is an edible tuberous plant; however, corms are its most worldwide consumed part while the corm powder is widely used in food industries. In this work, a sulphated polysaccharide extract of C. esculenta corm (SCE) was prepared and its cancer chemopreventive properties were explored. The amending of carcinogen metabolism and radical scavenging affinity revealed that SCE is a strong tumor anti-initiation agent via suppressing cytochrome P450-1A and enhancing glutathione and the carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…38 The sulfated chemically modified polysaccharide is shown in Table 4. Gamal-Eldeen et al 44 used the sulfation reagent formed by oleum and formamide to prepare taro sulfated-polysaccharide. The analysis results showed that the sulfate substitution rate was 48%, and the sulfation degree was 2.3.…”
Section: Structural Modification Of Taro Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The sulfated chemically modified polysaccharide is shown in Table 4. Gamal-Eldeen et al 44 used the sulfation reagent formed by oleum and formamide to prepare taro sulfated-polysaccharide. The analysis results showed that the sulfate substitution rate was 48%, and the sulfation degree was 2.3.…”
Section: Structural Modification Of Taro Polysaccharidesmentioning
confidence: 99%
“…The sulfated chemically modified polysaccharide is shown in Table 4. Gamal‐Eldeen et al 44 . used the sulfation reagent formed by oleum and formamide to prepare taro sulfated‐polysaccharide.…”
Section: Structural Modification Of Taro Polysaccharidesmentioning
confidence: 99%